1993
DOI: 10.1172/jci116358
|View full text |Cite
|
Sign up to set email alerts
|

The ionic mechanism of reperfusion-induced early afterdepolarizations in feline left ventricular hypertrophy.

Abstract: Left ventricular hypertrophy (LVH) potentiates reperfusionassociated ventricular fibrillation. To study the mechanism responsible, patch-clamp techniques were used to evaluate transmembrane ionic currents during "reperfusion" after a CN --induced metabolic surrogate for ischemia in isolated myocytes from a feline model of experimental LVH. Reperfusion caused the generation of early afterdepolarizations (EADs) from an average take-off potential of -33 mV in LVH cells but not in cells from normal hearts. 10 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 43 publications
0
22
0
2
Order By: Relevance
“…29 Observations in animal models suggest that cardiac myocytes from hypertrophied hearts develop abnormalities of repolarization, which could predispose to fatal arrhythmogenesis. 30 Similarly, it is conceivable that nonspecific interstitial fibrosis could contribute to the initiation of ventricular arrhythmias through a functional reentrant mechanism. 31 The presence of fibrosis in some component of the conduction system in 8 of 9 hearts subjected to a detailed conduction system examination suggests a propensity for bradycardia in some of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 Observations in animal models suggest that cardiac myocytes from hypertrophied hearts develop abnormalities of repolarization, which could predispose to fatal arrhythmogenesis. 30 Similarly, it is conceivable that nonspecific interstitial fibrosis could contribute to the initiation of ventricular arrhythmias through a functional reentrant mechanism. 31 The presence of fibrosis in some component of the conduction system in 8 of 9 hearts subjected to a detailed conduction system examination suggests a propensity for bradycardia in some of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…With either stable or unstable plaque conditions, myocardial perfusion variations that create sequences of ischemia and reperfusion initiate regional variations in myocardial cell membrane electrophysiology. 51 These variations contribute a transient substrate for triggered activity and reentry as the basis for initiating arrhythmias.…”
Section: Sca Associated With Transient Ischemiamentioning
confidence: 99%
“…52 In the latter, clinical and experimental evidence shows that the reperfusion phase is associated with lengthening of the time course of repolarization in the affected area, equivalent to a regional "long QT" in the ischemic area. 51 This contributes to the generation of triggered activity leading to polymorphic ventricular tachycardia, which in turn may initiate reentrant tachyarrhythmias leading to cardiac arrest. It is likely that transient ischemia and/or reperfusion are common mechanisms by which first coronary events express as SCD.…”
Section: Sca Associated With Transient Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that long-term administration of IGF-I regulates the expression of the K ϩ channel in cultured neonatal rat ventricular myocytes (18). Most studies regarding the electrophysiological alterations associated with cardiac hypertrophy were performed on the pressure-overload model, which has been associated with reduction in I to (6,15,16,53) and no change (6,57) or a decrease in I K (13,14,29,30) and I K1 (5,15,37). Interestingly, Brooksby et al (5) have shown that the electrical remodeling related to cardiac hypertrophy was restricted to a decrease in I K1 current density with no difference in the resting potential level of cardiomyocytes from control and spontaneously hypertensive rats.…”
mentioning
confidence: 99%